(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Coronary heart disease and cancer are leading causes of death worldwide. The combination of coronary heart disease (CHD) and oncopathology , given the prevalence of both nosologies, is not uncommon [2]. The presence of concomitant coronary artery disease in patients with malignant neoplasms in most cases serves as an aggravating factor, complicating and/or limiting the treatment of oncopathology [1]. Coronary artery disease in patients with oncopathology can increase the incidence of postoperative complications, in-hospital mortality, and also reduce long-term survival after radical surgery for malignant neoplasm. Myocardial revascularization , performed as the first stage in patients with hemodynamically significant coronary artery (CA) stenosis, is the main treatment method preventing the development of cardiovascular complications during and after oncopathology treatment .